9.4.5 problem problem 5

Internal problem ID [969]
Book : Differential equations and linear algebra, 4th ed., Edwards and Penney
Section : Section 7.3, The eigenvalue method for linear systems. Page 395
Problem number : problem 5
Date solved : Monday, January 27, 2025 at 03:22:39 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=6 x_{1} \left (t \right )-7 x_{2} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=x_{1} \left (t \right )-2 x_{2} \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.003 (sec). Leaf size: 34

dsolve([diff(x__1(t),t)=6*x__1(t)-7*x__2(t),diff(x__2(t),t)=x__1(t)-2*x__2(t)],singsol=all)
 
\begin{align*} x_{1} \left (t \right ) &= c_1 \,{\mathrm e}^{5 t}+c_2 \,{\mathrm e}^{-t} \\ x_{2} \left (t \right ) &= \frac {c_1 \,{\mathrm e}^{5 t}}{7}+c_2 \,{\mathrm e}^{-t} \\ \end{align*}

Solution by Mathematica

Time used: 0.003 (sec). Leaf size: 72

DSolve[{D[ x1[t],t]==6*x1[t]-7*x2[t],D[ x2[t],t]==x1[t]-2*x2[t]},{x1[t],x2[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} \text {x1}(t)\to \frac {1}{6} e^{-t} \left (c_1 \left (7 e^{6 t}-1\right )-7 c_2 \left (e^{6 t}-1\right )\right ) \\ \text {x2}(t)\to \frac {1}{6} e^{-t} \left (c_1 \left (e^{6 t}-1\right )-c_2 \left (e^{6 t}-7\right )\right ) \\ \end{align*}